2017
DOI: 10.1002/jgh3.12002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary beliefs and practices on patients with inflammatory bowel disease: An observational study from India

Abstract: Background and AimPatients with inflammatory bowel disease (IBD) are at a risk of nutritional deficits because of poor dietary beliefs and practices. There are no data on this aspect from Asia, which is experiencing a rise in IBD incidence. We aimed to establish dietary beliefs and practices in patients of IBD from India.MethodsPatients with ulcerative colitis (UC) and Crohn's disease (CD) followed up between November 2016 and March 2017 were included. A questionnaire extracted information on the patients' soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 18 publications
(28 reference statements)
3
35
0
Order By: Relevance
“…6,31 Besides, food avoidance may also one of the contributing factors to poorer dietary intake among patients in the active state. [15][16][17] However, in our study, overall we found that most of the "trigger foods" avoided were less than 30%, which are similar with several studies that reported the avoidance of milk products and red meat was 29% and 27%, respectively, 8 whereas avoidance towards oily/ fatty foods and sweetened beverages accounted for 20% and 27%, respectively. 32 Although the data just showed a small percentage of UC patients who avoided the "possible harmful foods," our study found that the practice of food avoidances was more frequent in those with clinically active disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6,31 Besides, food avoidance may also one of the contributing factors to poorer dietary intake among patients in the active state. [15][16][17] However, in our study, overall we found that most of the "trigger foods" avoided were less than 30%, which are similar with several studies that reported the avoidance of milk products and red meat was 29% and 27%, respectively, 8 whereas avoidance towards oily/ fatty foods and sweetened beverages accounted for 20% and 27%, respectively. 32 Although the data just showed a small percentage of UC patients who avoided the "possible harmful foods," our study found that the practice of food avoidances was more frequent in those with clinically active disease.…”
Section: Discussionsupporting
confidence: 90%
“…There are however a few studies available on the dietary beliefs and practices among IBD patients. [15][16][17] To the best of our knowledge, this is the first study conducted in Malaysia to assess the nutritional intake of UC patients according to disease states and food avoidance practices. Findings from this study can be used in formulating nutritional guidelines for UC patients in the future.…”
Section: Introductionmentioning
confidence: 99%
“…This new fact prompts IBD patients with a nutritional demand to be supervised and treated by a professional. Tomar et al [22] also concluded that proper dietary counselling is required in these patients to prevent malnutrition. From our results, however, it seems that finding a good diet for IBD patients is combining patient's own experiences (personalized diet) with external advice by a professional.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with IBD are unaware of the importance of diet in the management of IBD. In addition to this, common misperceptions can result in dietary changes leading to undernutrition in patients with IBD [ 105 ]. Nutritional deficiencies are more common in small bowel CD than colonic CD or UC, and therefore, nutritional care is important in the management of patients with IBD and in the prevention and treatment of malnutrition and micronutrient deficiencies and prevention of osteoporosis in adults and promotion of growth and development in children [ 27 , 106 – 109 ].…”
Section: The Asian Working Group Guidelines Regarding Diet In Inflammmentioning
confidence: 99%
“…A large majority of patients with IBD perceive food as a risk factor and impose dietary restrictions without proper counseling, which results in malnutrition [ 3 , 105 , 117 119 ]. However, there is little evidence from interventional studies to support specific dietary restrictions in IBD [ 120 ].…”
Section: The Asian Working Group Guidelines Regarding Diet In Inflammmentioning
confidence: 99%